PENGEMBANGAN MODUL MATA KULIAH METODOLOGI PENELITIAN PENDIDIKAN BERBASIS HIGH ORDER THINKING SKILL (HOTS) - Deni Adriani,dkk (Jurnal Pendidikan Ekonomi, 2019)
The purpose of this study is to find out (1) the design of learning modules based on High Order Thinking Skill (HOTS) courses in educational research methodology. (2) to develop a module of education research methodology courses based on High Order Thinking Skill (HOTS. The method used is the R & D method. This development procedure consists of 4-D (Four D Models). The results of research and development can be summarized as follows: (1) Development of research methodology modules based on high order thinking skills using the Four-D model. Define obtained that students need modules that can help students learn independently. Design, get the results of teaching materials that are in accordance with the needs of students in the form of a research methodology module based on high order thinking skills. Develop, validated by experts with a mean total score of 3.99 with appropriate categories and revised according to material expert advice, and trials limited to some students in class A of the fifth semester of economic education study program at Medan State University with a mean total score of 3.92 with good category. Disseminate, module dissemination for class A students in the fifth semester of the economic education study program from the experimental results revealed that learning outcomes after using modules were higher than before using modules with an average value of 72.98 pretests. Whereas for the posttest value obtained the average learning outcomes of 83.70. The number of students sampled was 43 people.